Structural, cellular and molecular aspects of immune privilege in the testis - Li, Nan; Wang, Tao; Han, Daishu (Frontiers in Immunology, 2012)
The testis presents a special immunological environment, considering its property of immune privilege that tolerates allo- and auto-antigens. Testicular immune privilege was once believed to be mainly based on the sequestration of antigens from the immune system by the blood-testis barrier in the seminiferous epithelium. Substantial evidence supports the view that the combination of physical structure, testicular cells, and cytokines controls immune responses in the testis to preserve the structural and functional integrity of testicular immune privilege. Both systemic immune tolerance and local immunosuppression help maintain the immune privilege status. Constitutive expression of anti-inflammatory factors in testicular cells is critical for local immunosuppression. However, the testis locally generates an efficient innate immune system against pathogens. Disruption of these mechanisms may lead to orchitis and impair fertility. This review article highlights the current understanding of structural, cellular and molecular mechanisms underlying the unique immune environment of the testis, particularly its immune privilege status.